2017
DOI: 10.1016/j.bpg.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and alcohol as risk factors for pancreatic cancer

Abstract: Pancreatic cancer is projected to become the leading cause of cancer deaths by 2050. The risk for pancreatic cancer may be reduced by up to 27% by modifying lifestyle risk factors, most notably tobacco smoking. Based on analysis of more than 2 million unselected individuals from general population, this article quantified the risk of pancreatic cancer in relation to lifelong tobacco smoking and alcohol consumption status, both alone and in combination. It also provided a state-of-the-art review of animal studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 52 publications
1
49
0
8
Order By: Relevance
“…Thus, PCLs may have the same risk factors with pancreatic cancer theoretically. Tobacco use, obesity, longstanding type 2 diabetes, and heavy use of alcohol are associated with significant increases in risk for pancreatic cancer . The smoking rate in China is much higher than in Western countries .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PCLs may have the same risk factors with pancreatic cancer theoretically. Tobacco use, obesity, longstanding type 2 diabetes, and heavy use of alcohol are associated with significant increases in risk for pancreatic cancer . The smoking rate in China is much higher than in Western countries .…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use, obesity, longstanding type 2 diabetes, and heavy use of alcohol are associated with significant increases in risk for pancreatic cancer. [21][22][23][24] The smoking rate in China is much higher than in Western countries. 25,26 On the contrary, the obesity rate in China is much lower than in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…40 The absence of data on other possible confounders, such as alcohol use, diabetes, physical activity, and dietary composition, is also a limitation. 37,[41][42][43][44][45][46] Smoking by itself also may interact with obesity to potentiate oxidative stress. 39 However, it has been demonstrated that SES (which was accounted for in our analysis) is strongly associated with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…32,35,36 We did not have data on the smoking status of participants, and smoking is a well known risk factor for pancreatic cancer in a dose-dependent manner. 37,[41][42][43][44][45][46] Smoking by itself also may interact with obesity to potentiate oxidative stress. 40 The absence of data on other possible confounders, such as alcohol use, diabetes, physical activity, and dietary composition, is also a limitation.…”
Section: Figurementioning
confidence: 99%
“…[31,32] Detailed radiotherapy or chemotherapy regimens were not available from the SEER database. In addition, other known risk factors for prognosis, such as family history [33], tobacco or alcohol [34] were also hard to obtain from the SEER database. Moreover, in this study, patients were randomly divided into two groups, 70% of them were used to construct and other 30% were used to validate the nomograms.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%